Towards synchrotron phase‐contrast lung imaging in patients – a proof‐of‐concept study on porcine lungs in a human‐scale chest phantom. (24th October 2018) - Wagner, Willi L.; Wuennemann, Felix; Pacilé, Serena; Albers, Jonas; Arfelli, Fulvia; Dreossi, Diego; Biederer, Jürgen; Konietzke, Philip; Stiller, Wolfram; Wielpütz, Mark O.; Accardo, Agostino; Confalonieri, Marco; et al.
Abstract : This proof‐of‐concept study on a human‐scale chest phantom and fresh porcine lungs with artificial pulmonary nodules demonstrates that local‐area in‐line free propagation phase‐contrast synchrotron tomography of fresh porcine lungs can be performed with an acceptable X‐ray dose that would allow for future application in patients while providing spatial‐resolution magnitudes higher than currently available clinical computed tomography scanners. Abstract : In‐line free propagation phase‐contrast synchrotron tomography of the lungs has been shown to provide superior image quality compared with attenuation‐based computed tomography (CT) in small‐animal studies. The present study was performed to prove the applicability on a human‐patient scale using a chest phantom with ventilated fresh porcine lungs. Local areas of interest were imaged with a pixel size of 100 µm, yielding a high‐resolution depiction of anatomical hallmarks of healthy lungs and artificial lung nodules. Details like fine spiculations into surrounding alveolar spaces were shown on a micrometre scale. Minor differences in artificial lung nodule density were detected by phase retrieval. Since we only applied a fraction of the X‐ray dose used for clinical high‐resolution CT scans, it is believed that this approach may become applicable to the detailed assessment of focal lung lesions in patients in the future.